An Interesting Observation Regarding Retrograde Vertebral Artery Flow in Patients With Dialysis Access Fistulas. (25th February 2019) - Naidich, James B.; Weiss, Amanda; Molmenti, Ernesto P.; Naidich, Jason J.; Pellerito, John S.
Abstract : Objectives: Retrograde vertebral artery flow, the steal phenomenon, is most frequently caused by a flow‐limiting stenosis of the proximal subclavian artery. The reversal of flow can be incomplete, resulting in bidirectional flow: retrograde in systole and antegrade in diastole. Less often, retrograde vertebral artery flow is the consequence of increased subclavian flow, as might occur with a well‐functioning dialysis access fistula. Our objective was to evaluate bidirectional vertebral artery flow associated with dialysis access fistulas. Methods: We retrospectively reviewed the direction of flow through the vertebral artery in systole and diastole of 335 patients with dialysis fistulas who had undergone extracranial cerebral vascular Doppler examinations. Results: Fifteen patients had retrograde flow in their vertebral artery ipsilateral with the side of their fistula. There was completely reversed flow in 1 patient and bidirectional flow in the other 14. For each of these 14, the flow was antegrade in early systole and retrograde in diastole. Compression of the fistula restored the antegrade flow. Conclusions: Under conditions of reduced subclavian artery flow, bidirectional vertebral artery flow will be retrograde in early systole and antegrade in diastole. Under conditions of increased subclavian artery flow, bidirectional flow through the vertebral artery will be antegrade in early systole and retrograde in diastole.